Preliminary results on relationship between thermal diffusivity and porosity of sea ice in the Antarctic - Liqiong, Shi; Yila, Bai; Zhijun, Li; Bin, Cheng; Matti, Lepparanta (Polar Research Institute of China - PRIC, 2009)
The in situ sea - ice temperature, salinity and density observed from Chinese Antarctic Zhongshan Station have been applied to calculate the vertical profile of sea ice porosity. Based on numerical method, a number of schemes on sea - ice thermal diffusivity versus porosity have been accessed and one optimized scheme is identified by an optimal control model with an advanced distributing parameter system. For simplicity, the internal heating source item was neglected in the heat conduction equation during the identification procedure. In order to illustrate the applicability of this identified scheme, the vertical ice temperature profiles have been simulated and compared with measurements, respectively by using identified scheme and by classical thermodynamic formulae. The comparisons indicated that the scheme describing sea - ice thermal diffusivity and porosity is reasonable. In spite of a minor improvement of accuracy of results against in situ data, the identified scheme has a more physical meaning and could be used potentially in various applications.